Comparative Assessment of Literal vs. Interpretive Approaches in English Translations of the Holy Quran - Asim Mahdi Al- Hilali, Lect. (lark, 2026)
Translating the Quranic Text into English comes up with a peculiar set of challenges due to its sacred nature and the huge gap on both the linguistic and cultural levels, between Arabic as an SL formulated in a Classical form and its counterpart TL (modern English in our case ). The present study aims to carry out a comparative evaluation between the two main approaches ( literal and interpretive ) as employed in the English translated versions of the Holy Quran. The Focus is placed chiefly on such well-known translations as  Marmaduke Pickthall’s  (1930), Abdullah Yusuf Ali’s (1934–1938), and Muhammad Asad’s (1980)—but also at the same time exploring such contributions as those provided by Arthur John Arberry (1955), Muhammad Abdel Haleem (2005), and others—the study includes an analysis of how various translation strategies would influence the transfer of Qur‘anic meaning. Based on the translation theory, especially the notion introduced by Eugene Nida of formal versus dynamic equivalence, the paper endeavors to establish that it is improbable to find a fully literal or fully interpretive translation. Rather, a spectrum of Translation and each translation of the Quranic text into English naturally exists at one place or another between the two edges of that spectrum. It is concluded that, on the one hand, the adoption of the approach of literal translation would normally result in preserving the lexical fidelity to the original, whereas the result of adopting the approach of interpretive translation is achieving greater success in the rendition of the spiritual effect and the functional meaning of the Quranic text for TL receivers(The English audience).
Keywords: Quranic Text, comparative assessment, literal approach